JAEPL, Vol. 1, Winter 1995-1996 - Alice G. Brand (Editor) (Journal of the Assembly for Expanded Perspectives on Learning, 1995)
Essays Mary C. Doane. Writing Reality: Constructivism, Metaphor, and Cosmology. Two philosophies of metaphor are contrasted in constructing discourse and reality. Derek Owens. Earthworm Hermeneutics. As an alternative to recent misreadings of boundary politics, a more responsible, outsider pedagogy needs to be cultivated. Tim Doherty. Strictly Ballroom? Dancing Along the Borders of Movement and Writing. Multiple intelligences are exercised when movement and writing intersect in the composition curriculum. Ellen W. Kaplan. The Subversive Play: Using Play, Dream, and the Body in the Classroom. The as-if world of play brings body-centered knowledge into the expressive writing class. Randi Patterson and Kim Jernigan . The Found Play: Learning and Teaching the Value of Reading and Writing. The "found" play is designed to make explicit the interpretive strategies that students use in everyday life, in a literary work, and in critical reading and writing. Frances Jo Grossman. Apples, Cupcakes, and Beige: Subjectivity and Academic Discourse. The relationship between intentional autobiographical reference and academic research yields a discourse called the writer-scholar's story of knowing. Anne Mullin. A Plea for Re-Form Aesthetics in the Writing Classroom. The emphasis on meaning and ideas should be refocused on form as an important aesthetic element in writing. Cramer Cauthen. Writing Ritual and the Cultural Unconscious: The Great Mother Archetype in the Composition Class. Jungian theory and feminist epistemology can be synthesized through their mythopoetic ways of making knowledge. Kristie S. Fleckenstein. Emotional Implication: Performing Within Emotional Gaps. The role of emotional implication is a process by which writers leave and fill emotional gaps within a text, thus creating their readers, text worlds, and themselves. Linda T. Calendrillo. Mental Imagery, Psychology, and Rhetoric: An Examination of Recurring Problems. The parallel debates on mental imagery in contemporary psychology and classical rhetoric have led to its marginal status in composition studies. Hildy Miller. Images at the Heart of Things: The Writer's Unconscious Speaking. Two case studies depict ways in which mental imagery from a Jungian perspective influences writing. Martha Goff Stoner. Mastery: Or, Where Does True Wisdom Lie? Zen philosophy and contemporary physics heighten awareness of wisdom as a process not a product.